Reference Values of Noninvasive Myocardial Work Indices Measured by Echocardiography in Healthy Children - Cui, Cunying; Zheng, Qiang; Li, Yanan; Huang, Danqing; Hu, Yanbing; Wang, Ying; Liu, Rujie; Liu, Lin; Zhang, Lianzhong (Frontiers in Pediatrics, 2022)
Backgroud: Noninvasive myocardial work, estimated by left ventricular (LV) pressure-strain loop (PSL), has been introduced for assessing LV myocardial performance. Based on both blood pressure and speckle-tracking derived strain data, noninvasive myocardial work is considered to be less load-dependent than global longitudinal strain (GLS). In some conditions, such as hypertension or aortic coarctation, the increased afterload will affect strain measurements, and myocardial work can be served as a more robust metric. Objective: We prospectively recruited healthy children to explore the relationship between myocardial work indices and body size parameters, and to determine the reference values of noninvasive myocardial work indices in healthy children. Methods: 183 healthy children (aged 1–18 years, males: 52.5%) were enrolled in the study. Global work index (GWI), global constructive work (GCW), global wasted work (GWW), global work efficiency (GWE), were assessed by LVPSL and compared according to age and sex. Results: The mean for GWI was 1,448.7 ± 265.0 mm Hg%, 1,859.8 ± 290.7 mm Hg% for GCW, and the median (interquartile range) for GWW was 54.0 (33.0–82.0) mm Hg% and 97.0 (95.0–99.0) % for GWE. male had greater GWI and GCW) than female (1,572.5 ± 250.2 mm Hg% versus 1,312.2 ± 208.7 mm Hg% and 1,944.3 ± 299.2 mm Hg% versus 1,766.6 ± 251.5 mm Hg%, respectively, all P < 0.001). GWI and GCW were significantly correlated with baseline parameters, including age, height, weight, BSA, body mass index, heart rate, and blood pressure. After indexed to BSA, GWI (BSA), GCW (BSA) remained significantly negatively correlated with age (P < 0.001). Conclusions: we proposed the normal reference values and regression equations for GWI and GCW based on age and BSA in healthy children. This might provide a basis of reference for the evaluation of cardiac function in children with cardiopulmonary disease.